(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study has been undertaken to explore and assess the style of Ruskin Bond’s short stories on Nature. Any assessment of Ruskin Bond as a Nature Lover must necessarily go into the genre of his short story writing as it has evolved the scent of Himalayan Region. Bond’s imageries and sensuousness are not overshadowed by any symbolic representation of nature. They grow as a result of his love for and commitment to nature. He does not crush the spontaneity of nature imageries by associating it with double layer of meaning or a display of his learning. Beautiful and sensational vibes of nature stirs him that he loves to share with his readers.